Pengaruh Model Pembelajaran PBL terhadap Kemampuan Berpikir Kritis Siswa pada Pembelajaran IPA - Desnita, Desnita; Dhalimunthe, Khairun Nisyah; Putri, Kurnia; Zahra, Novita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by the issue of students being less capable in solving problems. Most students are not able to approach and find solutions to the problems they face. This study aims to analyze the influence of problem-based learning models on science learning outcomes in the sixth grade of Karya Bunda Private Elementary School. The research method used is experimental. There is a significant difference in the science communication abilities of sixth grade students taught using audiovisual media compared to those taught without audiovisual media, as evidenced by statistical data showing the average scores of both groups.